De passeata a agressão: o percurso discursivo de uma notícia - Teixeira, Cristina; Gomes, Isaltina Mello; Morais, Wilma (Cadernos de Linguagem e Sociedade, 2010)
Our objective in this paper is to examine the partiality of the television news and how it occurs. From a corpus consisting of a series of three TV news programs ”“ presented by Rede Globo Nordeste, in July 1997 ”“ about an incident which occurred during a demonstration of the Landless Movement (MST), we identify linguistic aspects that disclosed the partiality of the TV news. The analysis of the corpus allowed us to show that the different forms to nominate the referents operate significant discursive changes, much more than simple lexical or stylistic variation.